2005
DOI: 10.1111/j.0023-8333.2005.00292.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Performance of College Students Classified as ADHD, LD, and LD/ADHD in Foreign Language Courses

Abstract: In this study, college students classified as having attention deficit hyperactivity disorder (ADHD) who had fulfilled the foreign language (FL) requirement were compared with students classified as learning disabled (LD) or both LD and ADHD who had either substituted courses for the college FL requirement (petition) or had passed FL courses (nonpetition) on cognitive and academic achievement measures and in FL course grades. Findings revealed few between-group differences on the testing measures and also show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 43 publications
4
19
1
Order By: Relevance
“…Based on the initial findings, this study agrees with formerly published articles in that there were no overall significant differences to be found regarding ADHD symptoms and language performance (Javorsky, 1996Sparks et al, 2004Sparks et al, & 2005. However, this investigation revealed that once the data were analyzed from the perspective of gender there were statistically significant differences between certain groups of students.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Based on the initial findings, this study agrees with formerly published articles in that there were no overall significant differences to be found regarding ADHD symptoms and language performance (Javorsky, 1996Sparks et al, 2004Sparks et al, & 2005. However, this investigation revealed that once the data were analyzed from the perspective of gender there were statistically significant differences between certain groups of students.…”
Section: Resultssupporting
confidence: 90%
“…This result was consistent with those reported in earlier studies (e.g. Javorsky, 1996Sparks et al, 2004Sparks et al, & 2005 and would appear to support the contention that ADHD alone does not significantly account for poorer results when learning foreign languages.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations